SP2.2.2 Thyroid Ultrasound reporting – an audit of practice. (9th August 2022) - Oladeji, Emmanuel; Dunstan, Matthew; Katsos, Konstantinos; Tabbakh, Yasmin; Burney, Kashif; Jamal, Karim
Abstract: Aims: Ultrasound (US) is the first line investigation for evaluating thyroid nodules. British Thyroid Association (BTA) guidelines set out a structured characterisation of thyroid nodules to guide further investigation. We conducted a closed loop audit at a District General Hospital to assess compliance of US reporting with BTA guidelines. Methods: 208 examinations were retrospectively analysed in the initial audit cycle. The reports were assessed for U status; number, measurements, characteristics and locations of nodules; comment on lymph nodes; whether FNA was performed or recommended; FNA histology; and the number of examinations performed by each radiologist/radiographer. Departmental teaching was then provided. A re-audit of 100 thyroid ultrasounds was then conducted. Results: In the initial audit and re-audit, respectively, the number of reporting clinicians decreased from 21 to 15, however the vast majority had reported fewer than 5 scans in each time period. Where nodules were present, the use of U classification in reports increased from 32.5% to 85.3%. Reporting of measurements, characteristics and location of nodules increased from 86.4%, 92.9% and 96.8% to 96.0%, 100.0% and 100.0% of reports, respectively. In both audits, 4.5% of U1/2 nodules were recommended for FNA. For U3–5 nodules, FNA or referral to specialty increased from 71.4% to 75.0%. Comment on lymph nodes increased from 89.4% to 95.9%. Conclusions: Following education, improvement in compliance was seen in nearly all domains, particularly in the utilisation of U classification. Further work is needed regarding the appropriate use of FNA, and caseload variation between clinicians.